A Comparative Study of Port Environmental Management in Canada and China - Gao, Yue (University of Waterloo, 2008)
Ports are the foreign gateway for countries and regions, and it is playing an increasingly important role in the world economy. While embracing the economic benefits brought by port development, Chinese ports are also faced with an unprecedented number of environmental problems. The overall goal of this thesis is to explore the similarities and differences between Canadian and Chinese ports in terms of their environmental protection policies, environmental management, and environmental protection measures. The thesis also aims to sum up valuable environmental protection experiences from both countries, in an effort to provide a reference guide for environmental protection activities in China. In this paper, many research methods have been used, including a review of the literature, site inspection, expert advice and case analysis in order to explore the similarities and differences in policies, concepts and measurements of port environmental protection in Canada and China. This information will be used to define the advanced concepts, managerial methods and measurements of environmental protection in Canada that Chinese government departments and port authorities could learn from. Through this study, suggestions will be made regarding what China's port sectors can learn from Canada in the following areas: (1) connecting port authorities with relevant environmental protection experts to carry out environmental protection research; (2) expanding the scope of port environmental protection, paying attention to co-operation with other agencies to protect the environment; (3) enhancing the protection of the ecological environment of the port， (4) paying attention to public participation in the process of port environmental protection; and (5) upgrading the environmental protection management concept on the part of port managers. It will be suggested that from Canada, relevant Chinese government departments should learn to (1) promulgate operational laws and regulations related to port environmental protection; (2) set up port management institutions to improve the port environmental management; (3) clarify the role of government departments, ports and environmental regulatory authorities in the course of the environmental protection; and (4) strengthen enforcement and regulations. In addition, it will be suggested that the enhancement of public awareness regarding environmental protection be continued and that relevant laws be passed to expand the scope of public participation.
Keywords: port environmental protection policies; port environmental management; port environmental protection measures; Planning